2009
DOI: 10.1597/07-215.1
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Obstructive Sleep Apnea in Preschool Children with Cleft Palate

Abstract: Preschool children with cleft lip and/or palate have a risk of obstructive sleep apnea that is as much as five times that of children without cleft. Obstructive sleep apnea appears to be underrecognized in this group of children. Further research is needed to investigate important risk factors for obstructive sleep apnea in children with cleft lip and/or palate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(67 citation statements)
references
References 47 publications
1
62
0
4
Order By: Relevance
“…d) One meta-analysis identified craniofacial characteristics consistent with OSAS [28], whereas a second meta-analysis suggested that the differences between children with SDB and controls are of marginal clinical significance [29]. e) All relevant publications are of class III or IV [30][31][32]. Not all studies concluded that repair of cleft palate increases the risk of OSAS [32][33][34].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…d) One meta-analysis identified craniofacial characteristics consistent with OSAS [28], whereas a second meta-analysis suggested that the differences between children with SDB and controls are of marginal clinical significance [29]. e) All relevant publications are of class III or IV [30][31][32]. Not all studies concluded that repair of cleft palate increases the risk of OSAS [32][33][34].…”
Section: Literature Reviewmentioning
confidence: 99%
“…e) All relevant publications are of class III or IV [30][31][32]. Not all studies concluded that repair of cleft palate increases the risk of OSAS [32][33][34].…”
Section: Literature Reviewmentioning
confidence: 99%
“…10,12,13 These anatomical differences may place these patients at increased risk of SDB, with studies estimating the risk of OSA to be between 22% and 65% in infants and children with CP/L. 7,14,15 In addition to being at risk of OSA because of congenital anatomical differences, patients with CP/L are at additional increased risk secondary to surgical procedures performed to help correct or repair the cleft and to improve speech. Approximately 10% to 35% of children with CP/L require surgery for velopharyngeal insufficiency (VPI), [16][17][18] usually through procedures such as palatoplasty, pharyngeal flap, and sphincter pharyngoplasty.…”
Section: Leep-disordered Breathingmentioning
confidence: 99%
“…3,4 The SDB prevalence in this study is consistent with the range of 22% to 65% reported in other studies. 7,14,15 The youngest age group, 0 to 2 years old, had the largest number of patients diagnosed as having SDB; however, this group had the fewest patients undergoing PSG. All the patients who underwent PSG from this age group had abnormal results.…”
Section: Commentmentioning
confidence: 99%
“…Children with cleft lip and/or palate (CL/P) are known to be at increased risk for sleep disordered breathing and/or OSA [2][3][4][5][6][7][8][9], with a recent study showing that 14.7% of children with isolated CL/P screened positive for OSA [7]. Abnormal craniofacial structure and anatomic changes to the nose, nasopharynx, oropharynx, and/or palate associated with CL/P may contribute to airway obstruction.…”
Section: Introductionmentioning
confidence: 99%